Health and web for women: preliminary results of "SEI Donna" survey. (13th November 2019) - Covolo, L; Guana, M; Bonaccorsi, G; Brunelli, L; Castaldi, S; De Donno, A; Mereu, A; Verani, M; Zaniboni, D; Gelatti, U
Abstract: Background: In 2018, 52% of the European population use the Web to seek health information and 77% consider it a useful tool to improve their knowledge about health. The Italian survey "SEI Donna" aims to investigate knowledge, perceptions and use of the web tools in women regarding health issues. Methods: We used an online questionnaire to collect data including the type of online research and the degree of trust towards different sources. We also assessed health literacy (HL) and eHealth literacy scale (eHEALS) using validated tests. Results: Of 7291 women who completed the questionnaire, 96% (n = 7022) seeks health information online. The 33% of women follows social media groups on health. One third of sample (31%) purchased a health product online, particularly cosmetics (75%) and supplements (41%). More than one third of sample thinks that information retrieved by web improve their health (35%) and influence their habits (34%). Half of sample (52%) searched online for a second opinion after medical examination. The reason was the need of a deepening in the 67% of cases. Overall, the HL is functional in 34% of cases, marginal in 56% and low in the rest (10%). Women with low HL trust less health information reported by institutional websites than women with functional HL, respectively 73% vs 86% (p < 0.001) and the eHEALS score of women less trusting is lower than those trusting, 23±7 vs 28±7 (p < 0.001). One third of women declares not to be able to evaluate the reliability of a website particularly women with low HL (36%) compared to those with functional HL (20%), p < 0.001. Women reporting not to be able to evaluate the reliability of a website have eHEALS score lower than women who indicated an institutional website, respectively 24±7 vs 28±7 (p < 0.001). Conclusions: The results confirm the large use of the web as a tool to seek health information, have a second opinion and buy health products. A good level of HL and eHEALS seem to make women more skilled in surfing the web. Key messages: The results confirm the importance to put effort on strategies aiming to improve health literacy and eHealth literacy in the population. In the public health communication perspective, the fact that one third of women thinks that information retrieved by web improve their health and influence their habits, must be considered.